Perlindungan Hukum terhadap Konsumen dalam Jual Beli Barang Melalui E-Commerce - I Putu Erick Sanjaya Putra; I Nyoman Putu Budiartha; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2019)
The Constitution of the Republic of Indonesia in 1945 article 1 paragraph 3, which reads "the State of Indonesia is a country of laws". This means that all members of society must be based on the law. The modern era of globalization, this versatile, all human activities have to be implemented quickly and easily. Selling is one of the fulfillment of human needs. E-Commerce is the business model of modern non-face (do not bring the perpetrators of the attempt to physically or real). Is there any formulation raised namely (1) How the legal sale and setting items through e-commerce? (2) How legal protection for consumers who suffered losses due to selling of goods e-commerce? Research methods used are normative, approach to research legislation, researching yet details rules governing consumer protection against businesses trading online, and then processed and analyzed with the use of interpretation and legal argumentation systematically as well as poured are descriptive. The results of this study are sale of goods law setting through Electronic Commerce (E-Commerce) have been set up in the ACT ITE and UUPK. legal protection for consumers who suffered losses due to the trading of goods electronic commerce (e-commerce) in the ACT ITE has been regulated in article 28 paragraph 1 regarding the losses consumers in e-commerce. As it known article 19 UUPK is set the compensation responsibility.